Expert opinion on NSCLC small specimen biomarker testing - Part 1: Tissue collection and management - Penault-Llorca, Frédérique; Kerr, Keith M; Garrido, Pilar; Thunnissen, Erik; Dequeker, Elisabeth; Normanno, Nicola; Patton, Simon J; Fairley, Jenni; Kapp, Joshua; de Ridder, Daniëlle; Ryška, Aleš; Moch, Holger (Virchows Archiv, 2022)
Biomarker testing is crucial for treatment selection in advanced non-small cell lung cancer (NSCLC). However, the quantity of available tissue often presents a key constraint for patients with advanced disease, where minimally invasive tissue biopsy typically returns small samples. In Part 1 of this two-part series, we summarise evidence-based recommendations relating to small sample processing for patients with NSCLC. Generally, tissue biopsy techniques that deliver the greatest quantity and quality of tissue with the least risk to the patient should be selected. Rapid on-site evaluation can help to ensure sufficient sample quality and quantity. Sample processing should be managed according to biomarker testing requirements, because tissue fixation methodology influences downstream nucleic acid, protein and morphological analyses. Accordingly, 10% neutral buffered formalin is recommended as an appropriate fixative, and the duration of fixation is recommended not to exceed 24-48 h. Tissue sparing techniques, including the 'one biopsy per block' approach and small sample cutting protocols, can help preserve tissue. Cytological material (formalin-fixed paraffin-embedded [FFPE] cytology blocks and non-FFPE samples such as smears and touch preparations) can be an excellent source of nucleic acid, providing either primary or supplementary patient material to complete morphological and molecular diagnoses. Considerations on biomarker testing, reporting and quality assessment are discussed in Part 2.
Keywords: Humans; nemalobuněčný karcinom plic; Lung Neoplasms; fixace tkání; Expert Testimony; nádory plic; Tissue Fixation; Formaldehyde; formaldehyd; znalecký posudek; Paraffin Embedding; biologické markery; Carcinoma, Non-Small-Cell Lung; Fixatives; lidé; zalévání tkání do parafínu; fixativa; Nucleic Acids; Biomarkers; nukleové kyseliny